A polyamide composite plastic with good mechanical properties at high temperature and preparation method thereof
By modifying the polyamide and combining it with hydrogenated nitrile rubber, a polyamide composite plastic with good high-temperature mechanical properties is formed, which solves the problem of poor mechanical properties of hydrogenated nitrile rubber at high temperatures and achieves stable application at high temperatures .
Patent Information
- Application Number
- CN202310713092.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-16
AI Technical Summary
The existing hydrogenated nitrile rubber has poor mechanical properties under high temperature conditions, the existing modification methods are cumbersome and have limited effects, making it difficult to provide a fundamental solution.
By modifying the polyamide and modifying the hydrogenated nitrile rubber with the modified polyamide, a rubber-polyamide composite material is formed, and carbon black, vulcanizing agent, stearic acid, sulfur and additives are added. , polyamide composite plastic with good high-temperature mechanical properties was prepared, avoiding the cumbersome problems caused by the multiple addition of hydrogenated nitrile rubber.
It significantly improves the tensile strength and elongation of breaking polyamide composite plastic at high temperatures, maintains good mechanical stability, and does not change significantly even at high temperatures of 100℃, and is suitable for high temperature applications.
Smart Images

Figure BDA0004288505460000061 
Figure BDA0004288505460000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a polyamide composite plastic with good mechanical properties at high temperatures and a preparation method thereof. Background Art
[0002] Hydrogenated nitrile rubber (HNBR or HSN) is a product obtained by hydrogenating the carbon-carbon double bonds in the nitrile rubber molecular chain to saturate them, hence the name "highly saturated nitrile rubber." Compared to nitrile rubber, hydrogenated nitrile rubber has a higher degree of saturation, resulting in better high-temperature resistance and mechanical properties.
[0003] To improve the mechanical properties of hydrogenated nitrile butadiene rubber (HNBR) at high temperatures (e.g., 100°C), the prior art modifies HNBR by adding surface-modified reinforcing materials and plastics, using a relatively cumbersome multi-step preparation method. While this method can improve the tensile strength and elongation at break of the modified HNBR at room temperature to a certain extent, the tensile strength and elongation at break at 100°C are significantly lower than those at room temperature, which does not provide a fundamental solution to the use of HNBR at high temperatures.
[0004] Therefore, it is necessary to provide a new method for modifying hydrogenated nitrile rubber so that the prepared hydrogenated nitrile rubber composite material has good high-temperature mechanical properties. Summary of the Invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art.
[0006] The first object of the present invention is to provide a polyamide composite plastic having good mechanical properties at high temperatures.
[0007] The second object of the present invention is to provide a method for preparing a polyamide composite plastic having good mechanical properties at high temperatures.
[0008] The polyamide composite plastic described in the present invention is actually a rubber-polyamide composite material. The present invention first modifies the polyamide, and then uses the modified polyamide to modify the hydrogenated nitrile rubber. The resulting material has excellent high-temperature mechanical properties and avoids the problem of multiple additions of the hydrogenated nitrile rubber. This method can avoid the cumbersome problems caused by the multiple batch additions of the hydrogenated nitrile rubber.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0010] A polyamide composite plastic having good mechanical properties at high temperatures. The raw material components for preparing the polyamide composite plastic include, by weight, 100 parts of hydrogenated nitrile rubber, 3-10 parts of modified polyamide, 20-40 parts of carbon black, 3-8 parts of vulcanizing agent, 1-5 parts of stearic acid, 4-12 parts of sulfur, and 3-12 parts of auxiliary agent.
[0011] The preparation method of the modified polyamide comprises the following steps: mixing basalt fiber, γ-aminopropyltriethoxysilane, polyacrylate, water, and ethanol to obtain a mixture A; then mixing polyamide, polyethylene glycol, fullerene, butyl titanate, and water to obtain a mixture B; and then mixing the mixture A and the mixture B and drying them to obtain the modified polyamide.
[0012] The present invention grafts the amino groups in γ-aminopropyltriethoxysilane onto basalt fibers, and simultaneously uses polyethylene glycol and butyl titanate to surface-modify fullerene, so that the fullerene can be uniformly dispersed in polyamide. The basalt fibers after surface grafting modification can be uniformly and stably dispersed in the polyamide. Fullerene's excellent ability to gain and lose electrons and its extremely symmetrical structure cooperate with the metal oxide components in basalt fiber (basalt fiber is composed of oxides such as silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, iron oxide and titanium dioxide. The zero-dimensional fullerene structure is not only uniformly dispersed on or near the surface of the basalt fiber, but the electron-deficient characteristics of the fullerene can produce electronic interactions with the metal elements in the basalt fiber, which is beneficial to maintaining the stability of the mechanical properties of the rubber-plastic system at high temperatures). Modified polyamide is prepared in polyamide. The modified polyamide is further added to hydrogenated nitrile rubber. In the presence of other raw material components, a uniform spatial network structure of the rubber-plastic system (i.e., polyamide composite plastic) is formed, thereby significantly improving the high-temperature mechanical stability of the polyamide composite plastic. Even at a high temperature of 100°C, the tensile strength and elongation at break of the polyamide composite plastic do not change significantly compared to room temperature, which is beneficial to the application of polyamide composite plastics at high temperatures.
[0013] Preferably, the preparation method of the modified polyamide is as follows: basalt fiber, γ-aminopropyltriethoxysilane, polyacrylate, water, and ethanol are stirred and mixed at a weight ratio of 1: (1-5): (0.5-3): (5-10): (1-5) at 50-60°C for 2-5 hours to obtain a mixture A; then polyamide, polyethylene glycol, fullerene, butyl titanate, and water are stirred and mixed at a weight ratio of 10: (3-10): (0.2-1): (3-12): (5-15) at 70-80°C for 1-3 hours to obtain a mixture B; and then the mixture A and mixture B are mixed at a weight ratio of 1: (2-8) at a stirring speed of 1000-2000 rpm for 6-10 hours, and vacuum dried at 70-80°C for 8-10 hours to obtain the modified polyamide.
[0014] Preferably, the polyamide is selected from PA6 or PA66.
[0015] Preferably, the basalt fiber has a diameter of 12-18 μm and a length of 3-8 mm, for example, a diameter of 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, and a length of 5 mm, 6 mm.
[0016] Preferably, the carbon black is, for example, carbon black N330 or carbon black N220.
[0017] Preferably, the auxiliary agent includes dicumyl peroxide and triallyl isocyanurate.
[0018] Preferably, the raw material components for preparing the polyamide composite plastic further include 1-5 parts of an anti-aging agent.
[0019] Preferably, the anti-aging agent comprises SUNNOC anti-aging agent.
[0020] Preferably, the vulcanizing agent is selected from at least one of zinc oxide, magnesium oxide and calcium oxide.
[0021] Preferably, the acrylonitrile content in the hydrogenated butyronitrile is 19-50%; further preferably, the acrylonitrile content in the hydrogenated butyronitrile is 34-45%.
[0022] Preferably, the hydrogenated nitrile rubber is selected from Terban HNBR 1707 of Bayer or Zetpol HSN1010 or Zetpol HSN1020 of Zeon.
[0023] Preferably, the raw material components for preparing the polyamide composite plastic further include zirconium oxide. The addition of zirconium oxide is beneficial to strengthening the electronic interaction between fullerene and basalt fiber, thereby improving the high temperature mechanical stability of the polyamide composite plastic.
[0024] Preferably, a polyamide composite plastic having good mechanical properties at high temperature is prepared by using raw material components comprising, by weight, 100 parts of hydrogenated nitrile rubber, 3-10 parts of modified polyamide, 20-40 parts of filler, 3-8 parts of vulcanizing agent, 1-5 parts of stearic acid, 4-12 parts of sulfur, 3-12 parts of auxiliary agent, 1-5 parts of anti-aging agent, and 1-2 parts of zirconium oxide.
[0025] A method for preparing a polyamide composite plastic having good mechanical properties at high temperatures comprises the following steps:
[0026] The modified polyamide is added into an internal mixer and heated until the modified polyamide is melted, and then hydrogenated nitrile rubber is added for mixing, and then the remaining components are added, thinned, mixed, sheeted, and vulcanized to obtain the polyamide composite plastic.
[0027] Preferably, the mixing temperature is 195-225° C., and the mixing time is 5-10 minutes.
[0028] Preferably, the vulcanization temperature is 150-165° C., and the vulcanization time is 8-20 minutes.
[0029] Application of the above-mentioned polyamide composite plastics in chemical equipment.
[0030] Preferably, the chemical equipment utilizes the polyamide composite plastic to form sealing components.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The polyamide composite plastic of the present invention is a rubber-plastic system. The raw material components for preparing the polyamide composite plastic include fullerene, whose electron-deficient characteristics can produce electronic interactions with metal elements in basalt fibers, which is beneficial to maintaining the stability of the mechanical properties of the rubber-plastic system at high temperatures. Under the joint action of other raw material components, it is beneficial to form a uniform spatial network structure of the rubber-plastic system (i.e., the polyamide composite plastic), thereby significantly improving the high-temperature mechanical stability of the polyamide composite plastic. Even at a high temperature of 100°C, the tensile strength and elongation at break of the polyamide composite plastic do not change significantly compared to those at room temperature, which is beneficial to the application of the polyamide composite plastic at high temperatures.
[0033] (2) The addition of zirconium oxide is beneficial to strengthening the electronic interaction between fullerene and basalt fiber, thereby improving the high-temperature mechanical stability of polyamide composite plastics. DETAILED DESCRIPTION
[0034] In order to make the technical solution of the present invention more clearly understood by those skilled in the art, the following examples are given for illustration. It should be noted that the following examples do not limit the scope of protection claimed by the present invention.
[0035] Unless otherwise specified, the raw materials, reagents or devices used in the following examples and comparative examples can be obtained from conventional commercial channels or by existing known methods.
[0036] Example 1
[0037] A polyamide composite plastic having good mechanical properties at high temperatures. The raw material components for preparing the polyamide composite plastic include, by weight, 100 parts of hydrogenated nitrile rubber (Bayer Terban HNBR 1707), 5 parts of modified polyamide (PA6), 40 parts of carbon black (carbon black N330), 6 parts of a vulcanizing agent (3 parts of zinc oxide and 3 parts of magnesium oxide), 1 part of stearic acid, 5 parts of sulfur, and 5 parts of an additive (3 parts of dicumyl peroxide and 2 parts of triallyl isocyanurate).
[0038] The preparation method of the modified polyamide is as follows: basalt fiber (diameter 12 μm, length 4 mm), γ-aminopropyl triethoxysilane, polyacrylate, water, and ethanol are stirred at 60°C for 3 hours in a weight ratio of 1:4:2:5:1 to obtain a mixture A; then polyamide, polyethylene glycol, and fullerene C are added. 60 , butyl titanate and water in a weight ratio of 10:4:0.3:5:10 are stirred and mixed at 75°C for 2 hours to obtain a mixture B, and then the mixture A and the mixture B are mixed in a weight ratio of 1:2 at a stirring speed of 1000 rpm for 8 hours, and vacuum dried at 75°C for 10 hours to obtain a modified polyamide.
[0039] A method for preparing a polyamide composite plastic having good mechanical properties at high temperatures comprises the following steps:
[0040] The modified polyamide was added to an internal mixer and heated until the modified polyamide was melted, and then hydrogenated nitrile rubber was added and mixed at a mixing temperature of 210°C for 8 minutes. The remaining components were added and stirred, and triangular packages were made 6 times with a thin pass, mixed evenly, and the sheet was removed. Then, the sheet was vulcanized on a flat vulcanizer (thin pass, mixing, sheet removal, and vulcanization are conventional operations in this field). The vulcanization temperature was 163°C and the vulcanization time was 18 minutes to obtain a polyamide composite plastic.
[0041] Example 2
[0042] A polyamide composite plastic having good mechanical properties at high temperatures. The raw material components for preparing the polyamide composite plastic include, by weight: 100 parts of hydrogenated nitrile rubber (Zetpol HSN1010 from Zeon), 6 parts of modified polyamide (PA66), 35 parts of carbon black (carbon black N330), 7 parts of a vulcanizing agent (4 parts of zinc oxide and 3 parts of magnesium oxide), 2 parts of stearic acid, 6 parts of sulfur, 6 parts of an additive (4 parts of dicumyl peroxide and 2 parts of triallyl isocyanurate), and 3 parts of a SUNNOC anti-aging agent.
[0043] The preparation method of the modified polyamide is as follows: basalt fiber (diameter 15 μm, length 6 mm), γ-aminopropyl triethoxysilane, polyacrylate, water, and ethanol are stirred at 60°C for 4 hours in a weight ratio of 1:3:3:6:2 to obtain a mixture A; then polyamide, polyethylene glycol, and fullerene C are added. 60 , butyl titanate and water in a weight ratio of 10:5:0.5:6:10 are stirred and mixed at 78°C for 3 hours to obtain a mixture B, and then the mixture A and the mixture B are mixed in a weight ratio of 1:2.5 at a stirring speed of 1500 rpm for 8 hours, and vacuum dried at 76°C for 10 hours to obtain a modified polyamide.
[0044] A method for preparing a polyamide composite plastic having good mechanical properties at high temperatures comprises the following steps:
[0045] The modified polyamide was added into an internal mixer and heated until the modified polyamide was melted, and then hydrogenated nitrile rubber was added for mixing at a mixing temperature of 208°C for 9 minutes. The remaining components were then added and stirred and mixed. The mixture was triangularly packaged 5 times with a thin pass, mixed evenly, and sheeted. The mixture was then vulcanized on a flat vulcanizer at a vulcanization temperature of 162°C for 19 minutes to obtain a polyamide composite plastic.
[0046] Example 3
[0047] A polyamide composite plastic having good mechanical properties at high temperatures. The raw material components for preparing the polyamide composite plastic include, by weight: 100 parts of hydrogenated nitrile rubber (Bayer Terban HNBR 1707), 5 parts of modified polyamide (PA6), 40 parts of carbon black (carbon black N330), 6 parts of a vulcanizing agent (3 parts of zinc oxide and 3 parts of magnesium oxide), 1 part of stearic acid, 5 parts of sulfur, 5 parts of an auxiliary agent (3 parts of dicumyl peroxide and 2 parts of triallyl isocyanurate), and 1.5 parts of zirconium oxide.
[0048] The preparation method of the modified polyamide is as follows: basalt fiber (diameter 12 μm, length 4 mm), γ-aminopropyl triethoxysilane, polyacrylate, water, and ethanol are stirred at 60°C for 3 hours in a weight ratio of 1:4:2:5:1 to obtain a mixture A; then polyamide, polyethylene glycol, and fullerene C are added. 60 , butyl titanate and water in a weight ratio of 10:4:0.3:5:10 are stirred and mixed at 75°C for 2 hours to obtain a mixture B, and then the mixture A and the mixture B are mixed in a weight ratio of 1:2 at a stirring speed of 1000 rpm for 8 hours, and vacuum dried at 75°C for 10 hours to obtain a modified polyamide.
[0049] A method for preparing a polyamide composite plastic having good mechanical properties at high temperatures comprises the following steps:
[0050] The modified polyamide was added into an internal mixer and heated until the modified polyamide was melted, and then hydrogenated nitrile rubber was added for mixing at a mixing temperature of 210°C for 8 minutes. The remaining components were then added and stirred, and triangular packages were punched through the thin tube 6 times. The mixture was mixed evenly, and the sheet was removed. The product was then vulcanized on a flat vulcanizer at a vulcanization temperature of 163°C for 18 minutes to obtain a polyamide composite plastic.
[0051] Comparative Example 1
[0052] Compared with Example 1, the only difference of Comparative Example 1 is that an equal amount of γ-methacryloxypropyltrimethoxysilane is used in Comparative Example 1 to replace the γ-aminopropyltriethoxysilane in Example 1, and the rest of the process is the same as that of Example 1.
[0053] Comparative Example 2
[0054] Compared with Example 1, the only difference of Comparative Example 2 is that the basalt fibers and fullerenes in Example 1 are replaced by equal amounts of carbon nanotubes in Comparative Example 2, and the rest of the process is the same as that in Example 1.
[0055] Comparative Example 3
[0056] Compared with Example 1, the difference of Comparative Example 3 is that the preparation method of the modified polyamide in Comparative Example 3 is: equal amounts of basalt fiber, γ-aminopropyltriethoxysilane, fullerene C 60 The modified polyamide was obtained by direct mixing, and the remaining process was the same as in Example 1.
[0057] Product effect testing
[0058] 1. The polyamide composite plastics prepared in Examples 1-3 and Comparative Examples 1-3 were tested for Shore A hardness at room temperature (25°C) and high temperature (100°C). The results are shown in Table 1.
[0059] Table 1
[0060]
[0061] As can be seen from Table 1, the Shore A hardness of the polyamide composite plastics prepared in Examples 1-3 of the present invention at a high temperature of 100°C changes very little compared to that at a room temperature of 25°C, especially the Shore A hardness corresponding to Example 3 changes even less. However, the Shore A hardness of the polyamide composite plastics prepared in Comparative Examples 1-3 at a high temperature of 100°C changes significantly compared to that at a room temperature of 25°C. It can be seen from this that in the preparation process of the polyamide composite plastic of the present invention, γ-methacryloxypropyltrimethoxysilane cannot be used to replace γ-aminopropyltriethoxysilane, nor can carbon nanotubes be used to replace basalt fibers and fullerenes, and in the preparation process of the modified polyamide, basalt fibers, γ-aminopropyltriethoxysilane, fullerene C cannot be directly used alone. 60 The modified polyamide is prepared by direct mixing. The preparation method of the modified polyamide of the present invention has a significant impact on the high temperature stability of the prepared product.
[0062] 2. The polyamide composite plastics prepared in Examples 1, 3, and Comparative Examples 1-3 were tested for tensile strength and elongation at break at room temperature (25°C) and high temperature (100°C) in accordance with GB / T1701-2001. The results are shown in Table 2.
[0063] Table 2
[0064]
[0065] As can be seen from Table 2, the polyamide composite plastics prepared in Examples 1 and 3 of the present invention exhibit good tensile strength and elongation at break at both room temperature and a high temperature of 100°C. Even when the temperature rises from room temperature to 100°C, the change in tensile strength and elongation at break of the polyamide composite plastics is significantly less than that of Comparative Examples 1-3. Table 2 further demonstrates that the preparation method of the modified polyamide in the polyamide composite plastic of the present invention significantly affects the high-temperature mechanical stability of the polyamide composite plastic.
Claims
1. A polyamide composite plastic, characterized in that: The raw material components for preparing the polyamide composite plastic include, by weight: 100 parts of hydrogenated nitrile rubber, 3-10 parts of modified polyamide, 20-40 parts of carbon black, 3-8 parts of vulcanizing agent, 1-5 parts of stearic acid, 4-12 parts of sulfur, and 3-12 parts of auxiliary agent; The preparation method of the modified polyamide comprises the following steps: mixing basalt fiber, γ-aminopropyl triethoxysilane, polyacrylate, water and ethanol at a weight ratio of 1:(1-5):(0.5-3):(5-10):(1-5) at 50-60°C for 2-5 hours to obtain a mixture A; then mixing polyamide, polyethylene glycol, fullerene, butyl titanate and water at a weight ratio of 10:(3-10):(0.2-1):(3-12):(5-15) at 70-80°C for 1-3 hours to obtain a mixture B; then mixing the mixture A and the mixture B at a weight ratio of 1:(2-8), the mixing stirring speed being 1000-2000 rpm, the stirring time being 6-10 hours, and vacuum drying at 70-80°C for 8-10 hours to obtain the modified polyamide.
2. The polyamide composite plastic according to claim 1, characterized in that: The polyamide is selected from PA6 or PA66; the basalt fiber has a diameter of 12-18 μm and a length of 3-8 mm.
3. The polyamide composite plastic according to claim 1, characterized in that: The auxiliary agent includes dicumyl peroxide and triallyl isocyanurate; the raw material components for preparing the polyamide composite plastic also include 1-5 parts of an anti-aging agent.
4. The polyamide composite plastic according to claim 3, characterized in that: The raw material components for preparing the polyamide composite plastic also include zirconium oxide.
5. The method for preparing the polyamide composite plastic according to any one of claims 1 to 4, characterized in that: The following steps are involved: The modified polyamide is added into an internal mixer to heat and melt, and then hydrogenated nitrile rubber is added for mixing, and then the remaining components are added, thinned, mixed, sheeted, and vulcanized to obtain the polyamide composite plastic.
6. The preparation method according to claim 5, characterized in that: The mixing temperature is 195-225° C., and the mixing time is 5-10 minutes.
7. The preparation method according to claim 5, characterized in that: The vulcanization temperature is 150-165° C., and the vulcanization time is 8-20 minutes.
8. Use of the polyamide composite plastic according to any one of claims 1 to 4 in chemical equipment.
